Layers of meaning exhibit - Unidentified photographer (Colorado State University. Libraries, 2016)
Photograph of visitors viewing the 2016 exhibit, “Layers of Meaning: Color and Design in Guatemalan Textiles.”
Keywords: Fashion -- History; Fashion -- Exhibitions